ON SOME CHARACTERISTIC SUBGROUPS OF THE GROUP OF UPPER TRIANGULAR MATRICES - Kera, Samet; Trenčevski, Kostadin (Matematichki Bilten, 1999)
We define and describe a regular subgroup of the Lie group \(K_n(F)\) of \(n × n\) upper triangular real or complex matrices with one on the main diagonal. We find that the number of such subgroups is \(n!\) and we propose a construction of a graph over the set of these subgroups.